Altered Functional Connectivity of Fusiform Gyrus in Subjects with Amnestic Mild Cognitive Impairment: A Resting-State fMRI Study - Cai, Suping; Chong, Tao; Zhang, Yun; Li, Jun; von Deneen, Karen M.; Ren, Junchan; Dong, Minghao; Huang, Liyu, for the Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Human Neuroscience, 2015)
Visual cognition such as face recognition requires a high level of functional interaction between distributed regions of a network. It has been reported that the fusiform gyrus (FG) is an important brain area involved in facial cognition; altered connectivity of FG to some other regions may lead to a deficit in visual cognition especially face recognition. However, whether functional connectivity between the FG and other brain regions changes remains unclear during the resting state in amnestic mild cognitive impairment (aMCI) subjects. Here, we employed a resting state functional MRI (fMRI) to examine changes in functional connectivity of left/right FG comparing aMCI patients with age-matched control subjects. Forty-eight aMCI and thirty-eight control subjects from the Alzheimer’s disease Neuroimaging Initiative (ADNI) were analyzed. We focused on the correlation between low frequency fMRI signal fluctuations in the FG and those in all other brain regions. Compared to the control group, we found some discrepant regions in the aMCI group which presented increased or decreased connectivity with the left/right FG including the left precuneus, left lingual gyrus, right thalamus, supramarginal gyrus, left supplementary motor area, left inferior temporal gyrus, and left parahippocampus. More importantly, we also obtained that both left and right FG have increased functional connections with the left middle occipital gyrus (MOG) and right anterior cingulate gyrus (ACC) in aMCI patients. That was not a coincidence and might imply that the MOG and ACC also play a critical role in visual cognition, especially face recognition. These findings in a large part supported our hypothesis and provided a new insight in understanding the important subtype of MCI.